2020
DOI: 10.1074/jbc.ra120.016106
|View full text |Cite
|
Sign up to set email alerts
|

In crystallo screening for proline analog inhibitors of the proline cycle enzyme PYCR1

Abstract: Pyrroline-5-carboxylate reductase 1 (PYCR1) catalyzes the biosynthetic half-reaction of the proline cycle by reducing Δ1-pyrroline-5-carboxylate (P5C) to proline through the oxidation of NAD(P)H. Many cancers alter their proline metabolism by upregulating the proline cycle and proline biosynthesis, and knockdowns of PYCR1 lead to decreased cell proliferation. Thus, evidence is growing for PYCR1 as a potential cancer therapy target. Inhibitors of cancer targets are useful as chemical probes for studying cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…In addition to serine, glycine, and cysteine, several studies support that inhibiting proline biosynthesis in melanoma and breast cancers can impede cell growth (160)(161)(162). Furthermore, PYCR1 inhibitors with anticancer activity have been identified to explore the role of proline biosynthesis in AML (163,164). Nevertheless, limited information is available regarding the effect of inhibiting either enzymes involved in proline biosynthesis or directly restricting proline in AML.…”
Section: Restriction Of Other Neaas Derived From Glutamate Decrease Myeloid Leukemia Proliferationmentioning
confidence: 99%
“…In addition to serine, glycine, and cysteine, several studies support that inhibiting proline biosynthesis in melanoma and breast cancers can impede cell growth (160)(161)(162). Furthermore, PYCR1 inhibitors with anticancer activity have been identified to explore the role of proline biosynthesis in AML (163,164). Nevertheless, limited information is available regarding the effect of inhibiting either enzymes involved in proline biosynthesis or directly restricting proline in AML.…”
Section: Restriction Of Other Neaas Derived From Glutamate Decrease Myeloid Leukemia Proliferationmentioning
confidence: 99%
“…Arginase inhibitors are also available and undergoing clinical trials in cancer patients as an immunotherapeutic, again, it will be interesting to discover if they also have an impact on CAFs. However, the development of drugs targeting the proline synthesis pathway is still at an early stage, and inhibitors against PYCR1 have only recently been developed (109,110). Since however, PYCR1 has recently been found to be upregulated in many cancer cells and to have tumour promoting effects both in cancer cells and CAFs (59,111,112), the development of new inhibitors may prove useful in targeting both tumour and stroma, killing two birds with one stone.…”
Section: Discussionmentioning
confidence: 99%
“…As for targeting PYCR1, using X ray in crystallography screening, Christensen et al [14] recently identified five inhibitors, one of which, N-formyl-L-proline (NFLP), has a competitive (with P5C) inhibition constant of 100 µM. NFLP inhibition was shown to phenocopy the PYCR1 knockdown in breast cancer cells by inhibiting de novo Pro biosynthesis [15].…”
Section: Proline Starvationmentioning
confidence: 99%
“…Targeting Gln starvation using the GLS1 inhibitor BPTES resulted in the elevated expression of GLS1 [109]. Likewise, Pro depletion is associated with the up-regulation of PYCR1, which is the key enzyme for the biosynthesis of Pro [5,14]. The re-expression of these once-silenced genes is to replenish the needed amino acids that cause the starvation.…”
Section: Re-activation Of the Silenced Genesmentioning
confidence: 99%